2010
DOI: 10.1523/jneurosci.bc-5668-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Automaticity Is a Matter of Timing

Abstract: There has been a long controversy concerning whether the amygdala's response to emotional stimuli is automatic or dependent on attentional load. Using magnoencephalography and an advanced beamformer source localization technique, we found that amygdala automaticity was a function of time: while early amygdala responding to emotional stimuli (40 -140 ms) was unaffected by attentional load, later amygdala response (280 -410 ms), subsequent to frontoparietal cortex activity, was modulated by attentional load.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
100
2
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(114 citation statements)
references
References 41 publications
8
100
2
3
Order By: Relevance
“…This was demonstrated by an increase in amygdala activation (which may reflect increased salience 21,22 ) and a decrease in IFG activation (which may reflect reduced reappraisal and inhibition [23][24][25] ) during the processing of positive pictures and a decrease in amygdala activation (associated with decreased salience) and an increase in IFG activation (reappraisal and greater inhibition) during the processing of negative pictures. The present study's findings with escitalopram and negative pictures are consistent with those of previous pharmacofMRI studies that found decreased amygdala activation in response to negative pictures after a single dose of fluvoxamine 31 and citalopram 40 and negative faces after a single dose 11 or a 7-to 10-day 38 treatment of citalopram.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was demonstrated by an increase in amygdala activation (which may reflect increased salience 21,22 ) and a decrease in IFG activation (which may reflect reduced reappraisal and inhibition [23][24][25] ) during the processing of positive pictures and a decrease in amygdala activation (associated with decreased salience) and an increase in IFG activation (reappraisal and greater inhibition) during the processing of negative pictures. The present study's findings with escitalopram and negative pictures are consistent with those of previous pharmacofMRI studies that found decreased amygdala activation in response to negative pictures after a single dose of fluvoxamine 31 and citalopram 40 and negative faces after a single dose 11 or a 7-to 10-day 38 treatment of citalopram.…”
Section: Discussionmentioning
confidence: 99%
“…The amygdala and inferior frontal gyrus (IFG) are key regions implicated in emotion reactivity and its appraisal and regulation, respectively, 19,20 and are regions modulated by single dose SSRI administration. 17 While the amygdala reliably and automatically 21,22 responds to the salience of affective stimuli, the IFG exerts top-down executive control over appraisal and affective responses. [23][24][25] Critically, the IFG plays an important role in attenuating amygdala activity in response to affective stimuli, facilitating effective appraisal and regulation.…”
Section: Introductionmentioning
confidence: 99%
“…This is a serious limitation when studying emotions, as nonconscious emotional processing takes place within milliseconds after stimulus onset in subcortical brain areas, including the amygdala and structures related to reflex-like motor reactions, and is followed shortly after by later responses engaged in more deliberate responses and in conscious vision (Borgomaneri, Gazzola, & Avenanti 2014;Borgomaneri, Vitale, Gazzola, & Avenanti, 2015;Garrido, Barnes, Sahani, & Dolan, 2012;Garvert, Friston, Dolan, & Garrido, 2014;Luo, Holroyd, Jones, Hendler, & Blair, 2007;Maior, Hori, Tomaz, Ono, & Nishijo, 2010;Nguyen et al, 2014). Because both early nonconscious and later conscious responses take place within the time window of a single volume acquisition in fMRI studies, the different functional values of neural activity in the same structure may be integrated or overridden (Brosch & Wieser, 2011;Costa et al, 2014;Luo et al, 2010).…”
Section: Methodological Issues In the Study Of Affective Blindsightmentioning
confidence: 99%
“…Another study revealed dissociation between rapid amygdala responses to automatic fearful face processing and later responses that interacted with voluntary attention. In fact, a rapid increase in gamma band activity in response to threatening faces (30-60 ms) was shown to be independent of task load, while a significant interaction of emotion with attention manipulation was seen at later latencies (280-340 ms) (Luo et al, 2010). Finally, two recent MEG studies used dynamic causal modeling (DCM) to test the explanatory power of the subcortical route to amygdala versus a model predicting only cortical mediation over amygdala activity.…”
Section: Timing and Speed Of Processing Along The Subcortical Pathwaymentioning
confidence: 99%
“…For instance, according to LeDoux' (1996) account, it is plausible that only the initial rapid orienting response would be determined by subcortical processes that are encapsulated from cognitive top-down control (Low Road; also see Luo et al, 2010). By contrast, maintaining or disengaging attention commences at a later stage and could be influenced by topdown goals, because potential threats are eventually also cognitively evaluated in the cortex (High Road; see also Carrasco, 2011, for a similar view).…”
mentioning
confidence: 99%